ANALISIS PERILAKU KONSUMTIF GENERASI Z di KABUPATEN KUNINGAN - Komarudin, Munir Nur; Wiharno, Herma; Nugraha, Mr.; Masruroh, Rina; Amanah, Anisa Dwi (Universitas Kuningan, 2024)
This research aims to determine the influence of financial literacy, self-control and income on the consumer behavior of Generation Z in Kuningan Regency. The research method used in this research is the descriptive and verification method with a quantitative approach. The population of this study is all Generation Z in Kuningan Regency with a total of 184,884. The number of samples used the Slovin technique with sample collection using accidental sampling technique. The type of data used in this research is primary data by distributing questionnaires to 100 respondents. The results of this study show that (1) financial literacy, self-control and income have an effect on consumptive behavior (2) Financial literacy has a negative and significant effect on consumptive behavior, (3) Self-control has a negative and significant effect on consumptive behavior, (4) Income has an effect positive and significant towards consumer behavior,